Retrospective study of endoscopic treatment in children with primary vesicoureteral reflux and multivariate analysis of factors for failure. (December 2014) - Akin, Yigit; Gulmez, Hakan; Güntekin, Erol; Baykara, Mehmet; Yucel, Selcuk
Abstract Objective. The aim of this study was to investigate endoscopic treatment in children with primary vesicoureteral reflux (VUR) and conduct a multivariate analysis of factors for failure. Material and methods. Between August 2006 and January 2012, 216 children (32 boys and 184 girls) with primary VUR (grades I–IV) who underwent endoscopic treatment were analysed. Patients with grade V VUR were excluded. Hydrodistension tests and intraureteral injection techniques were performed, if applicable. Urinary ultrasound and voiding cystourethrography were studied 3–6 months after surgery. Univariate and multivariate logistic regression were used for statistical analyses. Results. In total, 172 children (21 boys and 151 girls) were enrolled, and 280 ureters were treated (108 bilateral, 64 unilateral; three with grade I, 34 with grade II, 214 with grade III and 29 with grade IV VUR). The median (± SD) age was 7.8 ± 3.1 years (boys 7 ± 3.1 years, girls 7.9 ± 3.1 years). The mean (± SD) follow-up was 24.4 ± 4.1 months (boys 28.2 ± 8.1 months, girls 21.4 ± 4.1 months). Mean injected volume per ureter was 1.8 ± 0.5 ml. A single injection resolved the reflux in 79.6% and a second injection resolved it in 90.4% of ureters. Eight children (4.6%) had postoperative febrile urinary tract infections (fUTIs). Postoperative fUTIs were significantly associated with failures in injection (p < 0.001). Renal scars were significantly associated with postoperative fUTI (p = 0.006). Haematuria occurred in three children (minor complication); a non-functional kidney was observed in one child (major complication) and a laparoscopic nephrectomy was performed. Fourteen children underwent ureteroneocystostomy owing to unsuccessful VUR treatment. Conclusions. Endoscopic injection of small-diameter microsphere (80–120 μm) non-animal dextranomer–hyaluronic acid copolymer seems to be an effective treatment for VUR. Only postoperative fUTI and the presence of a renal scar were correlated with failed endoscopic treatment of VUR.